"Dust people": Samburu perspectives on disaster, identity, and landscape. Issue 1 (2nd January 2016) - Straight, Bilinda; Lane, Paul; Hilton, Charles; Letua, Musa
ABSTRACT: This paper discusses a Samburu pastoralist landscape idiom, ntoror, that encapsulates ideas about agentive pastoralist landscapes that inherently attract conflict; and passionate, place-based identities forged out of environmental and human-wrought disaster. The paper grows out of a project that experimentally integrated ethnographic self-scrutiny with a bio-archaeological excavation involving human remains, with the aim of encouraging reciprocal knowledge production. The inspiration for exploring ntoror and expanding its metaphorical reach came from our Samburu co-author, Musa Letua, who responded to the challenges the excavation posed by drawing upon the idiom of ntoror, which made sense to him. The overlapping stories of ntoror we narrate follow closely the ways in which Letua explored them in interviews associated with the excavation, and in other interview settings in earlier years. As such, this paper represents the fruits of cross-cultural collaboration and shared knowledge production.